Tinjauan Yuridis Perkosaan dalam Perkawinan (Marital Rape) Menurut Hukum Positif Indonesia - Mitchell Elieser Tumengkol; Yoan Barbara Runtunuwu; Hendrasari Brafely Rivan Rawung (Pusat Riset dan Inovasi Nasional, 2025)
Marital rape is a form of sexual violence that remains a controversial issue in Indonesia. The traditional view that considers sexual relations within marriage as a wife's obligation has hampered the recognition and enforcement of marital rape cases. This study aims to analyze the recognition and regulation of marital rape in Indonesian positive law and to identify the main factors that cause these cases. The research method used is normative legal research with a descriptive analytical approach, which focuses on the analysis of relevant laws and legal theories. The results of the study indicate that the regulation of rape in national law still experiences inconsistencies. The old Criminal Code (KUHP) does not recognize marital rape as a crime, while new recognition appears in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law) and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (TPKS Law). However, the provisions in the PKDRT Law that make marital rape a complaint-based offense still hinder victims in obtaining justice. The 2023 Criminal Code (KUHP) has included marital rape as a crime, but retains its complaint-based nature, indicating weak legal protection for victims. The main factors contributing to marital rape include power imbalances within the household, the wife's economic dependence on her husband, a patriarchal culture that assumes the husband has absolute rights over his wife's body, and a lack of legal awareness and protection mechanisms for victims.